1972
DOI: 10.1139/z72-007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides in the Lygaeinae (Hemiptera: Lygaeidae)

Abstract: Cardiac glycosides are shown to occur in brightly colored species belonging in most genera of the Lygaeid subfamily Lygaeinae. These insects appear to sequester these chemicals from their host plants. Several genera possess a special series of glands which appear to have as a principal function the concentration of these potent chemicals. Cardiac glycosides can also be detected in the other better known defensive secretions of these Hemiptera. It is concluded that most genera of Lygaeinae contain species that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 22 publications
1
56
0
4
Order By: Relevance
“…We found that seven of the nine Lygaeinae tested here store the orally ingested cardenolides ouabain and digoxin in their body. This supports earlier findings of Scudder & Duffey [9] who detected cardenolides in dried museum specimens of more than 20 genera of Lygaeinae. The lack of sequestration in A. longiceps and A. melanocephalus found here is in line with the life history of these two species which live on plants not known to produce cardenolides (Platanus: Platanaceae, or Ulmus: Ulmaceae, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that seven of the nine Lygaeinae tested here store the orally ingested cardenolides ouabain and digoxin in their body. This supports earlier findings of Scudder & Duffey [9] who detected cardenolides in dried museum specimens of more than 20 genera of Lygaeinae. The lack of sequestration in A. longiceps and A. melanocephalus found here is in line with the life history of these two species which live on plants not known to produce cardenolides (Platanus: Platanaceae, or Ulmus: Ulmaceae, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The majority (80%) of the species of Lygaeinae represented in our phylogeny (figure 1) are reported to use hosts in the Apocynaceae ( [9,35,36], J. Deckert 2014, personal observation). By contrast, A. longiceps and A. melanocephalus do not use Apocynaceae throughout their life cycle but are associated with Platanus (Platanaceae) or Ulmus (Ulmaceae) [36].…”
Section: (D) Host Plant Recordsmentioning
confidence: 97%
See 1 more Smart Citation
“…This work focused on species of brightly coloured, red and black Lygaeinae such as Oncopeltus fasciatus (Dallas) and emphasized the defensive role of the cardiac glycoside heart poisons that these bugs sequester from milkweed plants. Geoff and his students showed how these insects are adapted to living on these poisonous plants (Scudder and Duffey 1972;Isman et al 1977), how they isolate and sequester the cardenolide chemicals (Scudder and Meredith 1982), and how they use these chemicals in their defence against predators ( Moore and Scudder 1985;Scudder et al 1986). …”
Section: Researcher Writer and Field Biologistmentioning
confidence: 99%
“…Ces études concernaient surtout les Lygaeinae à coloration brillante rouge et noire, tels qu'Oncopeltus fasciatus (Dallas), et s'intéressaient principalement au rôle des glucosides cardiaques toxiques que ces insectes obtiennent des asclépiades. Geoff et ses étudiants ont pu démontrer comment ces insectes sont adaptés à vivre sur ces plantes toxiques (Scudder et Duffey 1972;Isman et al 1977), comment ils isolent et mettent sous séquestre les cardénolides (Scudder et Meredith 1982) et comment ils utilisent ces substances pour se défendre contre les prédateurs (Moore et Scudder 1985;Scudder et al 1986). …”
Section: Chercheur éCrivain Et Biologiste De Terrainunclassified